Relationship between echocardiographic characteristics and cardiac biomarkers during long-distance trail running - Jouffroy, Romain; Hergault, Hélène; Antero, Juliana; Vieillard Baron, Antoine; Mansencal, Nicolas (Frontiers in Cardiovascular Medicine, 2022)
Background Even if the beneficial cardiovascular effects of moderate exercise are recognized, the effects of prolonged and intense exercise are still debated. This study aims to assess the relation between echocardiographic parameters and cardiac biomarkers during a long-distance trail running. Methods We performed a prospective observational study including 20 participants (median age of 41 years old, still alive after a clinical 7-year follow-up) from an 80-km trail running. All subjects underwent an echocardiographic examination and venous blood sampling before the race, at the intermediate refreshment checkpoints of the race (21st and 53rd km) and within 10 minutes after arrival. Results Mitral E/A velocities ratio and mitral TDI e’ wave were significantly decreased from 21 km to arrival (p<0.05). Mitral S wave and global longitudinal strain significantly decreased from 53 km to arrival (p<0.05 for 53rd and 80th km). As compared to baseline, T-troponin and NT-proBNP significantly increased since the 21st kilometre for all participants, but T-troponin values systematically increased above the significative threshold. Diastolic echocardiographic abnormalities were mainly observed among patients with the highest NT-proBNP (> 77ng.l-1) values since the 21st kilometre. As compared to baseline, mitral e’ wave significantly decreased (-35%) in subjects with the highest values of NT-proBNP. Similarly, global longitudinal strain was also depressed among patients with the highest troponin values since the 53st kilometre (p = 0.01 for 53rd kilometre and p = 0.04 for arrival). Conclusions During a long-distance trail running, an early LV decrease of diastolic echocardiographic parameters is associated with an increase of NT pro-BNP blood levels, and a latter decrease of LV systolic echocardiographic parameters associated with an increase of T-troponin blood levels.